PENGARUH MODEL PEMBELAJARAN POGIL BERBANTUAN MEDIA PERMAINAN TTS TERHADAP HASIL BELAJAR IPA SISWA KELAS V SD - Ni Made Tini Sulasmi (Universitas Pendidikan Ganesha, 2018)
This study aimed at determining the effect of learning model POGIL assisted by crossword puzzle game media toward the learning outcome of natural science grade V primary students in Cluster IV Cempaka Putih, Kubutambahan Sub-district, Buleleng Regency in academic year 2017/2018. This research type was quasi experiment with post test only control group design. The population of this research were the students of grade V of primary school in Cluster IV Cempaka Putih, in academic year 2017/2018 amounting to 168 students. Sample determination was done by random sampling through lottery technique. The instrument of data collection used in this research was objective test. The data obtained were analyzed by descriptive statistical analysis, prerequisite test of data analysis, and hypothesis test through t-test. The results showed that there were significant differences of learning outcome of natural science between groups of students who were taught by POGIL learning model assisted by the media of crossword puzzle and groups of students who were not taught by the learning model of POGIL assisted by the media of crossword puzzles. It was seen from result of t-test calculation obtained tcount = 5,103 and ttable = 2.012 (ttcount> ttable). The differences in the learning outcome of natural science students indicated that the POGIL learning model assisted by crossword puzzle media had a positive effect on learning outcome of natural science on students.